Colonic volvulus and jejunal ischemia secondary to a congenital adhesive band - M. Grageda; V. Castro; N. Cordero; Z. Acun; M. Choudhary; M. Saeed; J. Bibawy; F. Velcek (Elsevier, 2020)
We report the case of a 7-year old Hispanic boy who presented with acute, severe intermittent diffuse abdominal pain. There was no previous significant medical or surgical history. Physical examination revealed a soft abdomen, normoactive bowel sounds, and epigastric tenderness. Initial blood tests and abdominal imaging were non-contributory, except for focal loops of dilated small bowel in the mid-abdomen. In less than 24 hours, the patient had worsening symptoms and physical findings. Emergent laparotomy revealed colonic volvulus with infarction and proximal jejunal ischemia secondary to a congenital adhesive band. Volvulus reduction, band release, extended right hemicolectomy, terminal ileostomy, and Hartman closure of the splenic flexure were performed. Recombinant tissue plasminogen activator (tPA) was infused into partially ischemic jejunum mesenteric vessels, and second look laparotomy planned. During the second laparotomy, nitroglycerin was topically applied on the ischemic jejunum, tPA infused into affected vessels, and third look laparotomy planned. Interval improvement of the affected proximal jejunum led to a shorter resection during the third laparotomy.Congenital adhesive bands are rare abnormalities that can cause bowel obstruction in children. A high index of suspicion in the absence of previous trauma or operations may prevent delays in diagnosis and treatment, allowing for improved outcomes.